2017
DOI: 10.1038/npp.2017.160
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Polyunsaturated Fatty Acids in Youths with Attention Deficit Hyperactivity Disorder: a Systematic Review and Meta-Analysis of Clinical Trials and Biological Studies

Abstract: The role of omega-3 polyunsaturated fatty acids (omega-3 or n-3 PUFAs) in the pathogenesis and treatment of children and adolescents with attention deficit hyperactivity disorder (ADHD) is unclear. A systematic review followed by meta-analysis was conducted on: 1) randomized controlled trials (RCTs) assessing the effects of n-3 PUFAs on clinical symptoms and cognition in children and adolescent with ADHD; and 2) case-control studies assessing the levels of n-3 PUFAs in blood and buccal tissues of children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
147
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(164 citation statements)
references
References 53 publications
14
147
1
2
Order By: Relevance
“…No meta‐analyses directly compared nutrient supplementation to psychotropic medications. All studies were placebo‐controlled.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No meta‐analyses directly compared nutrient supplementation to psychotropic medications. All studies were placebo‐controlled.…”
Section: Resultsmentioning
confidence: 99%
“…Specific psychiatric conditions (and reported outcomes) considered in this meta‐review included: schizophrenia (examining total symptoms along with positive, negative, general and depressive symptoms, and tardive dyskinesia); states at risk for psychosis (examining attenuated psychosis symptoms, negative symptoms, transition to psychosis, and functioning); depressive disorders (including any clinical depression, diagnosed major depressive disorder (MDD), depression in pregnancy, in old age, or as a comorbidity to chronic health conditions); anxiety and stress‐related conditions (including generalized anxiety disorder, obsessive‐compulsive disorder (OCD) and trichotillomania); bipolar disorder type I and II (examining overall symptoms, bipolar mania, bipolar depression, functional impairments, and quality of life); and ADHD (including composite symptoms, hyperactivity‐impulsivity, inattention, behavioural comorbidities such as aggression, and cognitive functioning).…”
Section: Resultsmentioning
confidence: 99%
“…These findings have implications beyond mood disorders and are compatible with the RDoC emphasis advocated by NIMH. EF impairment is a prominent characteristic of ADHD, and ADHD symptoms have been responsive to omega‐3 supplementation with small effect (Bloch & Qawasmi, ; Chang et al., ). Most study participants had comorbid ADHD; however, ADHD comorbidity did not significantly influence treatment outcome despite conferring nominally greater benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Ω3 supplementation trials have suggested benefit for childhood MDD and bipolar disorders (Clayton et al., ; Fristad et al., , ; Nemets, Nemets, Apter, Bracha, & Belmaker, ), working memory improvement in young adults (Narendran, Frankle, Mason, Muldoon, & Moghaddam, ), and modest but significant improvement of ADHD symptoms (Chang, Su, Mondelli, & Pariante, ). The primary trials from which the current analyses stem demonstrated significant improvement in bipolar depression with Ω3 supplementation and small–moderate improvement in unipolar depression; there was no treatment impact on mania (Fristad et al., , ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that a number of treatment effects may have failed to reach statistical significance due to small sample sizes and within and between study heterogeneity in terms of design and study participants (218) . In seven RCTs involving 534 adolescents with ADHD, very long chain n-3 fatty acids improved ADHD clinical symptom scores, while in three RCTs involving 214 adolescents, very long chain n-3 fatty acids improved cognitive measures associated with attention (219) . A very recent systematic review was supportive of use of n-3 fatty acid supplements in children with ADHD (220) .…”
Section: Neurocognitive Healthmentioning
confidence: 99%